A group of serum proteins as potential diagnostic biomarkers for Yin‐deficiency‐heat syndrome. Issue 8 (10th January 2020) - Chen, Jing; Jiang, Ting‐Ting; Yi, Wen‐Jing; Jiao, Jin‐Ling; Liu, Chang‐Ming; Tu, Hui‐Hui; Hu, Yu‐Ting; Shi, Li‐Ying; Huang, Huai; Li, Zhi‐Bin; Gan, Lin; Li, Zhong‐Jie; et al.
Abstract: Yin‐deficiency‐heat (YDH) syndrome is a very common subhealth status in Traditional Chinese Medicine. However, currently, there is no unified standard for diagnosing YDH syndrome. We applied the iTRAQ‐2D LC–MS/MS method to explore the potential of serum protein profiles as biomarker for YDH syndrome. A total of 120 differentially expressed proteins (79 downregulated and 41 upregulated) were identified by the proteomic profiling. The results of KEGG pathway analysis showed that the functions of the differentially expressed proteins were mainly involved in complement and coagulation cascades. The clinical data showed that YDH syndrome was closely related to inflammation and coagulation, compared with the healthy controls. The ELISA validation results indicated that the expression levels of ALB, CFI, and KLKB1 were downregulated in the YDH syndrome group ( p < .05). Moreover, we established a decision tree model based on the combination of these three proteins and achieved a sensitivity of 87.5%, a specificity of 84.4%, and AUC of 0.891. The results indicated that the combination of ALB, CFI, and KLKB1 may serve as potential biomarkers for diagnosing YDH syndrome. Our study can provide a new method for YDH syndrome diagnosis, and may also provide an experimental basis to understand the molecular mechanism of YDH syndrome.